MALE STERILITY 3 encodes a plant homeodomain‐finger protein for male fertility in soybean. Issue 5 (13th April 2022) - Hou, Jingjing; Fan, Weiwei; Ma, Ruirui; Li, Bing; Yuan, Zhihui; Huang, Wenxuan; Wu, Yueying; Hu, Quan; Lin, Chunjing; Zhao, Xingqi; Peng, Bao; Zhao, Limei; et al.
Abstract: Male‐sterile plants are used in hybrid breeding to improve yield in soybean ( Glycine max (L.) Merr.). Developing the capability to alter fertility under different environmental conditions could broaden germplasm resources and simplify hybrid production. However, molecular mechanisms potentially underlying such a system in soybean were unclear. Here, using positional cloning, we identified a gene, MALE STERILITY 3 ( MS3 ), which encodes a nuclear‐localized protein containing a plant homeodomain (PHD)‐finger domain. A spontaneous mutation in ms3 causing premature termination of MS3 translation and partial loss of the PHD‐finger. Transgenetic analysis indicated that MS3 knockout resulted in nonfunctional pollen and no self‐pollinated pods, and RNA‐seq analysis revealed that MS3 affects the expression of genes associated with carbohydrate metabolism. Strikingly, the fertility of mutant ms3 can restore under long‐d conditions. The mutant could thus be used to create a new, more stable photoperiod‐sensitive genic male sterility line for two‐line hybrid seed production, with significant impact on hybrid breeding and production. Abstract : Map‐based cloning showed that MALE STERILITY 3 (MS3) encodes a PHD‐finger protein for male fertility in soybean. CRISPR/Cas9‐mediated mutagenesis of MS3 resulted in a photoperiod‐sensitive genic male sterility phenotype that was rescued under long‐day conditions.